Human development report 2007/2008 fighting climate change : human solidarity in a divided world (New York United Nations Development Programme ; Palgrave Macmillan, 2007)
The report ...calls for a "twin track approach that combines stringent mitigation to limit 21st Century warming to less than 2AC (3.6A F) with strengthened international cooperation on adaptation. On mitigation, the authors call on developed countries to ... cut greenhouse gas emissions by at least 80% of 1990 levels by 2050. It advocates a mix of carbon taxation, more stringent cap-and-trade programmes, energy regulation, and international cooperation on financing for low-carbon technology transfer. Turning to adaptation, the report warns that inequalities in ability to cope with climate change are emerging as an increasingly powerful driver of wider inequalities between and within counties. It calls on rich countries to put climate change adaptation at the centre of international partnerships on poverty reduction.
Fighting climate change: human solidarity in a divided world -- The 21st Century climate challenge -- Climate shocks: risk and vulnerabililty in an unequal world -- Avoiding dangerous climate change: strategies for mitigation -- Adapting to the inevit able: national action and international cooperation.
Includes bibliographical references and index.
Keywords: United Nations Development Programme; Climatic changes -- Economic aspects; Climatic changes -- Environmental aspects; Global warming -- Economic aspects; Global warming -- Environmental aspects; Greenhouse gas mitigation